Inside Cover: Porous Organic Salts: Diversifying Void Structures and Environments (Angew. Chem. Int. Ed. 31/2022). Issue 31 (14th June 2022) - Ami, Takahiro; Oka, Kouki; Tsuchiya, Keiho; Tohnai, Norimitsu
Abstract : Porous organic salts (POSs) are porous organic materials, in which various aromatic sulfonic acids and amines are regularly self‐assembled by charge‐assisted hydrogen bonding. Norimitsu Tohnai and co‐workers demonstrate in their Research Article (e202202597 ) the advantages of diverse porous organic salts, such as all‐organic, extremely facile preparation methods, diverse void structures and environments, and excellent CO2 adsorption properties.